1983
DOI: 10.1042/bj2140183
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in food intake and in lipogenesis in mammary gland and liver of lactating rats

Abstract: Despite the hyperphagia, the food intake of the lactating rat showed marked diurnal changes which paralleled those of virgin rats. The major difference was that lactating rats consumed a higher proportion (35%) of their diet during the light period than did virgin rats (14%). The peak rate of lipogenesis in the lactating mammary gland occurred around midnight, and this decreased by 67% to reach a nadir around mid-afternoon; this corresponded with the period of lowest food intake. The diurnal variations in hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…However, our own and other studies have shown that non-lactating and lactating rats consume respectively about 85 and 65% of their food at night (Strubbe & Gorissen 1980, Munday & Williamson 1983, Pickavance et al 1996. From this, we estimate that our non-lactating rats would have eaten about 2 and 12 g/12 h during the light and dark periods respectively, and the lactating rats about 20 and 38 g/12 h during these periods.…”
Section: Effects Of Lactation On Hypothalamic Gene Expression: Relatimentioning
confidence: 58%
See 1 more Smart Citation
“…However, our own and other studies have shown that non-lactating and lactating rats consume respectively about 85 and 65% of their food at night (Strubbe & Gorissen 1980, Munday & Williamson 1983, Pickavance et al 1996. From this, we estimate that our non-lactating rats would have eaten about 2 and 12 g/12 h during the light and dark periods respectively, and the lactating rats about 20 and 38 g/12 h during these periods.…”
Section: Effects Of Lactation On Hypothalamic Gene Expression: Relatimentioning
confidence: 58%
“…Lactation increases food intake 3-to 4-fold in rats, reflecting the considerable nutritional demands of the mammary gland (Wade & Schneider 1992, Barber et al 1997, but the diurnal pattern of food intake persists, with about 65% of food still being consumed at night (Strubbe & Gorissen 1980, Munday & Williamson 1983, Pickavance et al 1996, Denis et al 2003a. Despite the hyperphagia, lactating rats enter and remain in a state of overall net negative energy balance (Barber et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, natural diurnal fluctuations in food intake (about a threefold decline between early morning and midday in rats) are accompanied by similar fluctuations in mammary lipogenesis (also about threefold, but with some delay). This must underlie much of the marked diurnal variation in maternal metabolic rate, judged by heat output, that so closely follows the changing food intake Munday and Williamson, 1983). A rise in the fat content of the diet also leads to a decline in mammary lipogenesis without, however, alteration of the chain-length profile of the newly synthesized fatty acids (Grigor and Warren, 1980;Agius and Williamson, 1980).…”
Section: Nutritionally Induced Changes In Fatty Acid Synthesismentioning
confidence: 99%
“…Indeed, the daytime serum leptin concentration has been reported to decrease by 20-75% during lactation in the rat (Kawai et al 1997, Pickavance et al 1998, Terada et al 1998, Woodside et al 1998, Brogan et al 1999, Herrera et al 2000, although others found no change (Chien et al 1997, Carmen-Garcia et al 2000. Rats, however, normally consume 80% or more of their food at night (Kimura et al 1970, Bruckdorfer et al 1974) and this pattern of eating is retained during lactation (Strubbe & Gorissen 1980, Munday & Williamson 1983, Pickavance et al 1996. Both adipose tissue leptin mRNA expression (Saladin et al 1995, Pickavance et al 1998, Xu et al 1999 and serum leptin concentration (Pickavance et al 1998, Xu et al 1999, Nagatani et al 2000, Nishiyama et al 2000, Mastronadi et al 2000, Pu et al 2000, Johnstone & Higuchi 2001, Kalsbeek et al 2001 show a diurnal rhythm in fed rats, increasing at night.…”
Section: Introductionmentioning
confidence: 99%